Contextual Marketing – Insights from Literature Review and Implications - Clifford, Monica Janet; Kavitha , R. (International Journal of Accounting and Economics Studies, 2025)
The proliferation of new technologies, such as personal digital assistants, or PDAs, and interactive television, amongst other things, has opened a wealth of potential for effectively targeting customers in real time while they are present in a virtual environment. This opens a lot of opportunities for businesses. Customers have access to the World Wide Web and the Internet through their wireless devices, no matter where they are or when they want to use them. Contextual marketing, often referred to as CM and commonly abbreviated as CM, is a strategy that entails providing customers with information that is both individualized and pertinent to their present position at the precise moment when customers need such information. This strategy is essential for luring in new clients and keeping the ones you already have. Clients in an economy that is already oversaturated with information demand not only knowledge, but also products and services that are relevant, personalized, and contextual at the time of purchase. The purpose of this research is to conduct a comprehensive review of the existing literature on contextual marketing in the preceding 20 years, focusing on both the global and the Indian contexts. The development and expansion of contextual marketing, as well as its contemporary consequences regarding earlier published works, are investigated. In the study, the systematic literature review approach of searching for relevant material is used. This research was carried out with the intention of conducting a comprehensive assessment of the existing literature with the purpose of ensuring that the fullest possible list of relevant studies is taken into consideration. To compile the papers comprising the systematic review, an algorithmic search strategy was utilized. An analysis of the previous research was carried out with the use of online databases such as Elsevier, Routledge, Emerald Group, Springer Nature, Sage, Directory of Open Access Journals, Semantic Scholar, Wiley, Academia, JSTOR, and Guildford Press. The study reaches its conclusion by providing a tangible theoretical foundation for contextual marketing while also outlining the ramifications that contextual marketing has in the modern digital world.